Real estate investment : a value based approach / G Jason Goddard, Bill Marcum - Goddard, G Jason
This book fills a gap in the existing resources available to students and professionals requiring an academically rigorous, but practically orientated source of knowledge about real estate finance. Written by a bank vice-president who for many years has practiced as a commercial lender and who teaches real estate investment at university level, and an academic whose area of study is finance and particularly valuation, this book will lead readers to truly understand the fundamentals of making a sound real estate investment decision. The focus is primarily on the valuation of leased properties such as apartment buildings, office buildings, retail centers, and warehouse space, rather than on owner occupied residential property.